INTEGRITAS SEBAGAI PEMODERASI PENGARUH PENGALAMAN AUDITOR PADA KUALITAS AUDIT - Dwitariani, I Gusti Agung; Suputra, I D. G. Dharma (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
This report aim ed to review auditor’s experience influenc e on the audit quality. In addition, the research - also aim ed to know whether integrity would moderating auditor’s experience influence on audit quality. The stu dy was d one in akun tan public office in B ali province. The sampel of in this research were 34 0f 98 external auditors . Sampling of the research is with the method of non probability sampling using to technique purposive sampling . The data collected using the method of survey with questionnaire technique. Moderating Regression Analysis (MRA) is used as the data analysis techniques According to the research analysis , it was found that auditor’s experience h ad some positive effects on the quality of audit . Integrity moderat ed ( strengthen ed ) the auditor experience influence in auditor quality. Integrity is pure moderators.
Keywords: Experience Auditors , Integrity, Audit Quality